ANALISIS NETWORK PLANNING DENGAN CRITICAL PATH METHOD (CPM) DALAM USAHA EFISIENSI WAKTU PADA PRODUKSI PRECAST DI PT XYZ - Safa’at Safa’at (STIE Mahardhika, 2020)
PT. XYZ is a company engaged in the field of Readymix and precast concrete or concrete ready to use and precast concrete. This research is aimed to evaluate and accelerate the execution time and the cost with the critical path method (CPM), hopefully the job execution time is faster with a more efficient cost. The method that is done is to interview the employees who are appropriate to the field and to collect the necessary documents, from the data is carried out evaluation and further remediation measures to accelerate the work and efficiency of costs. From the results of the study came the conclusion that with a critical path method (CPM) application, job execution time can be accelerated and cost more efficiently..